2015
DOI: 10.1080/15384101.2015.1053670
|View full text |Cite
|
Sign up to set email alerts
|

CTCF-dependent co-localization of canonical Smad signaling factors at architectural protein binding sites in D. melanogaster

Abstract: The transforming growth factor b (TGF-b) and bone morphogenetic protein (BMP) pathways transduce extracellular signals into tissue-specific transcriptional responses. During this process, signaling effector Smad proteins translocate into the nucleus to direct changes in transcription, but how and where they localize to DNA remain important questions. We have mapped Drosophila TGF-b signaling factors Mad, dSmad2, Medea, and Schnurri genome-wide in Kc cells and find that numerous sites for these factors overlap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…Specifically, HOX13 proteins did not regulate individual enhancers, but rather restructured the chromatin architecture of the locus in a way so that contacts with one (the telomeric) TAD were repressed, whereas contacts with the other (centromeric)TAD were promoted (Beccari et al 2016). A related observation was recently reported in Drosphila for CTCF/Cohesin and Smad-TFs, which are the transcriptional effectors of TGFß/BMP signalling (Van Bortle et al 2015). The Smad-TFs co-localized in a CTCF-dependent manner to CTCF binding sites within TADs and might be involved in sculpting the TAD to enable transcriptional regulation.…”
Section: Discussionsupporting
confidence: 72%
“…Specifically, HOX13 proteins did not regulate individual enhancers, but rather restructured the chromatin architecture of the locus in a way so that contacts with one (the telomeric) TAD were repressed, whereas contacts with the other (centromeric)TAD were promoted (Beccari et al 2016). A related observation was recently reported in Drosphila for CTCF/Cohesin and Smad-TFs, which are the transcriptional effectors of TGFß/BMP signalling (Van Bortle et al 2015). The Smad-TFs co-localized in a CTCF-dependent manner to CTCF binding sites within TADs and might be involved in sculpting the TAD to enable transcriptional regulation.…”
Section: Discussionsupporting
confidence: 72%
“…Medea interacts with Mad to mediate the transcriptional consequences of BMP/TGF-β signaling that is necessary for many developmental processes (Hamaratoglu et al, 2014). Using ChIP-seq data from cultured Kc cells in response to exogenous treatment with a Drosophila BMP, Decapentaplegic (DPP) (Van Bortle et al, 2015), we confirmed the overlap between KDM5 upregulated genes and those bound by Medea (p = 5e-4; Figures 5E and 5F). KDM5 may therefore act at a subset of BMP/Medea-regulated genes to facilitate transcriptional repression.…”
Section: Resultsmentioning
confidence: 59%
“…R program was used for Fisher’s exact test; Student’s t test, Wilcoxon rank-sum tests, and Pearson correlation analyses were carried out using GraphPad Prism, version 7. The accession number for the KDM5 ChIP-seq data is GEO: GSE70589 (Liu and Secombe, 2015), the accession number for the BEAF-32 ChIP-seq data is GEO: GSE16245 (Nègre et al, 2010), the accession number for the Medea ChIP-seq data is GEO: GSM1678114 (Van Bortle et al, 2015), and the accession number for the Myc ChIP and RNA-seq data is EMBL-EBI: E-MTAB-3209 (Herter et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…NRSF/REST is a component of a transcriptional repressor complex and is involved in negative regulation of mesenchymal stem cell differentiation (GO: 0017053, GO: 2000740). CTCF has epigenetic regulatory functions and maintains DNA methylation (GO: 0040030, GO: 0010216); in addition, SMAD proteins localize to CTCF binding sites in a CTCF dependent manner, which connects TGF-β/BMP/SMAD with CTCF and myofibroblast differentiation (Van Bortle et al, 2015). One of the genes CTCF binds is REST.…”
Section: Discussionmentioning
confidence: 99%